EVALUATION OF DRIP IRRIGATION SYSTEM FOR TION SYSTEM FOR TION SYSTEM FOR Broccoli Broccoli Broccoli UNDER Tarai arai CONDITION OF UTTARAKHAND - CHANDRA, RAVISH; P. K. , SINGH (The Bioscan, 2018)
Improved irrigation use efficiency is an important tool for intensifying and diversifying agriculture in India, resulting in higher economic yield from irrigated farmlands with a minimum input of water. A field experiment was conducted at experimental farm of college of Technology, G.B.P.U.A and T, Pantnagar to evaluate the performance of drip irrigation system installed for broccoli crop. The different uniformity indicators were Distribution Uniformity (DU), Christiansen’s Uniformity Coefficient (CUC), Wilcox & Swails Uniformity Coefficient (UCW) and Hart Uniformity Coefficient (UCH). The DU, CUC, UCW and UCH ranged from, 89.8 to 96.7, 92.4 to 97.8, 90.9 to 97.2 and 92.8 to 97.8 respectively. The highest crop yield for broccoli crop was reported in plot T1 R3 (Drip irrigation based on 100% evaporation replenishment) which is having higher DU, CUC, UCW and UCH values whereas lowest crop yield was reported in plot T3 R2 (Drip irrigation based on 60 % evaporation replenishment) having lowest DU, CUC, UCW and UCH values. Water production functions were developed for broccoli crop considering irrigation depth and spatial uniformity of water application under drip irrigation. The developed production functions can be used for predicting crop yield for different depth of irrigation and uniformity.